Exploring novel drug targets in fatty acid pathway of Plasmodium falciparum - Meenakshi Pradhan, I Arnold Emerson, R Kiruba Thangam, J Febin Prabhu Dass (Journal of Applied Pharmaceutical Science, 2015)
The malarial parasite Plasmodium falciparum infects humans and proliferates rapidly inside the host before its detection. The proliferation step requires a large amount of lipids for membrane synthesis. Thus fatty acid biosynthesis occurring in the apicoplast plays an important role in causing cerebral malaria. In this study, we explored and analyzed these pathways using stoichiometric matrix, elementary flux modes and robustness analysis. Based on the above analysis, the robustness of this pathway diminished as the result of virtual enzyme knock out indicating four key enzymes, 3-oxoacyl-ACP synthase, 3-oxoacyl-ACP synthase, 3-oxoacyl-ACP synthase and Glycerol-3-phosphate o-acyl transferase. Among the four, the first three are existing drug targets. Subsequently, we also found that a combinatorial double knock out of these enzymes predicts further reduction in overall pathway enzyme activity. Thus, we propose multi drug targeting as a better way to treat brain malaria.
Keywords: Stoichiometric matrix, Elementary Flux Modes, Drug Target, Malaria. Fatty Acid synthesis pathway.